Cellular senescence induced by CD158d reprograms natural killer cells to promote vascular remodeling - Rajagopalan, Sumati (National Academy of Sciences, 2012)
Natural killer (NK) cells, which have an essential role in immune defense, also contribute to reproductive success. NK cells are abundant at the maternal–fetal interface, where soluble HLA-G is produced by fetal trophoblast cells during early pregnancy. Soluble HLA-G induces a proinflammatory response in primary, resting NK cells on endocytosis into early endosomes where its receptor, CD158d, resides. CD158d initiates signaling through DNA-PKcs, Akt, and NF-κB for a proinflammatory and proangiogenic response. The physiological relevance of this endosomal signaling pathway, and how activation of CD158d through soluble ligands regulates NK cell fate and function is unknown. We show here that CD158d agonists trigger a DNA damage response signaling pathway involving cyclin-dependent kinase inhibitor p21 expression and heterochromatin protein HP1-γ phosphorylation. Sustained activation through CD158d induced morphological changes in NK cell shape and size, and survival in the absence of cell-cycle entry, all hallmarks of senescence, and a transcriptional signature of a senescence-associated secretory phenotype (SASP). SASP is a program that can be induced by oncogenes or DNA damage, and promotes growth arrest and tissue repair. The secretome of CD158d-stimulated senescent NK cells promoted vascular remodeling and angiogenesis as assessed by functional readouts of vascular permeability and endothelial cell tube formation. Retrospective analysis of the decidual NK cell transcriptome revealed a strong senescence signature. We propose that a positive function of senescence in healthy tissue is to favor reproduction through the sustained activation of NK cells to remodel maternal vasculature in early pregnancy.